Shelter from the Storm--but Disconnected from Jobs : Lessons from Urban South Africa on the Importance of Coordinating Housing and Transport Policies - Lall, Somik V. (World Bank, Washington, DC, 2012)
Informal settlements are a permanent feature of South Africa's cities. Estimates from the General Household Survey by Statistics South Africa show that more than 26 percent of all households in the country's six metropolitan areas live in informal dwellings. The government's policy efforts have focused on provision of subsidized housing, first introduced as part of the Reconstruction and Development Program. Through the lens of new urbanism and coordination in planning this paper explores the possible impact of the program using data from the General Household Survey. The analysis of the program's beneficiaries relative to non-beneficiaries does not show that public housing provision has multiplier effects in terms of complementary private investments in housing maintenance or in upgrading. This is likely because Reconstruction and Development Program housing is often far from employment centers, with the houses built in the "old" apartheid locations that are disconnected from employment centers. In addition, households do not receive title deeds and are not allowed to rent out these dwelling. On the demand side, the authors carried out a small sample survey in Cape Town and find that, on a per hectare basis, shack dwellers are paying around the same for access to land as can be found in the up-scale market for undeveloped land. However, land zoning regulations and subdivision laws do not allow supply of small plots that are compatible with the affordability of poor households.